Transforming microfinance institutions : providing full financial services to the poor - Ledgerwood, Joanna; White, Victoria (Washington, DC : World Bank : MicroFinance Network ; [Stockholm] : Sida, 2006)
This book presents a practical "how-to" manual for MFIs to develop the capacity to become licensed to intermediate deposits from the public. The authors also provide guidelines for regulators to license and supervise microfinance providers and for transforming MFIs to meet the demands of two major new stakeholders - regulators and shareholders.
Includes bibliographical references and index.
osa 03/05/13, ijb 26/02/2019
Loan
Keywords: Microfinance; Economic assistance, Domestic; Poverty; Developing countries